Assessment of key factors responsible for the pest status of the bean flower thrips megalurothrips sjostedti (thysanoptera: thripidae) in West Africa - Tamo, M.; Baumgärtner, J.; Delucchi, V.; Herren, H.R. (1993)
Megalurothrips sjostedti (Trybom) is an important pest of cowpea (Vigna unguiculata) in West Africa. Three key factors assumed to be responsible for its pest status are analysed, the survival on alternative host-plants during the dry season, the inefficient biotic mortality factors regulating population growth, and the effect of larval feeding on the development of cowpea flower buds. Extensive surveys indicate clearly that M. sjostedti survives the dry season on a wide range of alternative hosts all belonging to the Leguminosae, where it can feed and reproduce. Different antagonists were observed attacking eggs and larvae of M. sjostedti; their impact, however, is low and cannot prevent pest outbreaks. Two undescribed Megaphragma spp., and one Oligosita sp., all trichogrammatid egg parasitoids, were recorded for the first time. The anthocorid Orius sp. was the most important larval predator. No hymenopterous parasitoids could be reared from larvae collected on cowpea and three major alternative hosts, whereas a low percentage of the larvae collected from the flowers of Tephrosia candida, an exotic shrub native to India, were parasitized by the eulophid Ceranisus menes (Walker), also recorded for the first time in Africa. The feeding activity of six larvae of Megalurothrips sjostedti during five days induced the shedding of all flower buds of a cowpea inflorescence. The results of the analysis shed new light on the M. sjostedti pest problem, and the ways to solve it. The lack of efficient antagonists, particularly larval parasitoids known from closely related south-east Asian Megalurothrips spp., and the high damage threshold, indicate that M. sjostedti is a potential target for biological control. However, further studies are needed to investigate the migration of M. sjostedti adults to and from alternative host-plants, in order to reinforce the action of biocontrol with cultural pratices.